hsa-miR-518-5p/hsa-miR-3135b Regulates the REL/SOD2 Pathway in Ischemic Cerebral Infarction - Zhao, Boyan; Jiang, Xiaofan (Frontiers in Neurology, 2022)
Objectives: To investigate the pathways or genes that may play a role in ischemic stroke (IS), as well as the expression features of these critical genes, a bioinformatics technique based on single-cell analysis combined with bulk RNA-seq analysis was applied. Methods: To begin, researchers analyzed aberrantly regulated miRNAs and mRNAs using transcriptome data from the GEO database's ischemic brain infarction dataset. In mouse cerebrovascular monocytes, we used SCENIC to identify the key transcription factors (regulators). Then, using the transcription factors and RNAs that were shown to be differently expressed in bulk RNA, we built a miRNA-TF-mRNA interaction network. Molecular Complex Detection (MCODE) was also used to extract the network's core sub-networks and identify the important routes within the sub-networks. Finally, in our institution, whole blood samples were taken from 24 patients with ischemic stroke and 22 healthy control volunteers for confirmation of critical molecules in the route. Results: We found four cell types and 266 regulons in mouse cerebrovascular monocytes using SCENIC analysis. We found 112 differently expressed miRNAs and 3780 differentially expressed mRNAs in total RNA. Following that, we created a network of miRNA-TF-gene interactions. hsa-miR-518-5p&hsa-miR-3135b)/Rel/SOD2 were discovered to play a possible role in the progression of IS. Rel and SOD2 expression were confirmed to be elevated in the IS group in the clinical cohort (p 0.05). Rel expression was also found to be elevated in endothelial cells and fibroblasts at the single-cell level, indicating that it is a cell-specific regulon. Rel is primarily engaged in neurotransmitter activity and oxidative phosphorylation pathways, according to functional enrichment analyses. Conclusions: hsa-miR-518-5p/hsa-miR-3135b was discovered to possibly regulate the Rel/SOD2 pathway in the progression of IS.